The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1016/j.amsu.2016.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Association between elevated pre-operative glycosylated hemoglobin and post-operative infections after non-emergent surgery

Abstract: BackgroundA chronic state of impaired glucose metabolism affects multiple components of the immune system, possibly leading to an increased incidence of post-operative infections. Such infections increase morbidity, length of stay, and overall cost. This study evaluates the correlation between elevated pre-operative glycosylated hemoglobin (HbA1c) and post-operative infections.Study designAdult patients undergoing non-emergent procedures across all surgical subspecialties from January 2010 to July 2014 had a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 40 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…In terms of preoperative glycemic control for postoperative complications and postoperative length of hospital stay, a preoperative HbA1c level < 7.0% is an optimum indicator that can be used in reducing postoperative infectious complications in non-cardiac surgeries [ 26 ]. A chronic hyperglycemic state leads to impaired immune system, which contributes to the increased incidence of postoperative infections [ 26 , 27 ]. However, the results of the present study were not consistent with those of other studies.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of preoperative glycemic control for postoperative complications and postoperative length of hospital stay, a preoperative HbA1c level < 7.0% is an optimum indicator that can be used in reducing postoperative infectious complications in non-cardiac surgeries [ 26 ]. A chronic hyperglycemic state leads to impaired immune system, which contributes to the increased incidence of postoperative infections [ 26 , 27 ]. However, the results of the present study were not consistent with those of other studies.…”
Section: Discussionmentioning
confidence: 99%
“…All blood glucose values reported from the day of surgery and for 48 hours after surgery were collated to give a mean value of peri-operative glycemic control. For group analysis of peri-operative glycemic control, a mean value of ≤10 mmol/l was categorized as optimal control and a mean value of >10 mmol/l as sub-optimal control [ 5 ]. The admission glucose value, the maximum glucose value and HbA1c were also separately recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Pre-existing diabetes has been associated with increased risk of post-operative infection [ 2 - 4 ]. Poor control of underlying diabetes, measured as a raised glycosylated hemoglobin A1c (HbA1c) mmol/mol, also increases the risk of infection in some analysis but not all [ 5 , 6 ]. Efforts to better control the peri-operative glucose levels have been shown to decrease the incidence of post-operative infections [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although diabetes status is an independent risk factor for postoperative infections, multiple studies have shown that HbA1c does not correlate with infection, wound healing, or operative complication rate. 10,12,24 Thus, HbA1c may not adequately reveal the adverse effects of hyperglycemia, potentially masking opportunities for beneficial interventions in candidates for elective surgical procedures.…”
Section: Traditional Measures Of Glycemic Controlmentioning
confidence: 99%
“…This may explain the mixed results obtained in studies that have attempted to correlate HbA1c with adverse surgical outcomes. 912 Conversely, plasma glucose is simply a snapshot of control that is highly variable. Thus, the search continues for ideal measures of glycemic control.…”
Section: Introductionmentioning
confidence: 99%